Delivery of Bordetella pertussis adenylate cyclase toxin to target cells via outer membrane vesicles - Donato, Gina M. (2012)
B.pertussis adenylate cyclase toxin (ACT) intoxicates cells by producing intracellular cAMP. B.pertussis outer membrane vesicles (OMV) contain ACT on their surface (OMV-ACT), but the properties of OMV-ACT were previously unknown. We found that B.pertussis in the lung from a fatal pertussis case contains OMV, suggesting an involvement in pathogenesis. OMV-ACT and ACT intoxicate cells with and without the toxin’s receptor CD11b/CD18. Intoxication by ACT is blocked by antitoxin and anti-CD11b antibodies, but not by cytochalasin-D; in contrast, OMV-ACT is unaffected by either antibody and blocked by cytochalasin-D. Thus OMV-ACT can deliver ACT by processes distinct from those of ACT alone.